The Effect of the Use Single Identiity Number on the Achievement of Accountability of Kantor Pelayanan Pajak (KPP) Pratama (A Case Study At KPP Pratama Jakarta Kelapa Gading - Purnomo, Daniel; Harnaeni, Nani (SEAN Institute, 2024)
This research aims to find out the effect of the uses SIN on the achievement of accountability of KPP Pratama. The research was undertaken at KPP Pratama Jakarta Kelapa Gading, using 41 respondents of its employees. It is a case study research. The data was collected using the questionnaire and documentation technique. In this research simple linear regression and t-test measurement methods were used to examine the effect of independent variable on dependent variable, and were tested using 95% level of confidence or alpha 5%. The result reveals that there is a positive impact of of the uses SIN on the accountability achievement of KPP Pratama Jakarta Kelapa Gading. It was proven by the value of obtained t statistic 7,794 ≥ 1,691 of t table and the probability value 0,000 ≤ 0,05, showing that zero hypothesis was rejected and alternative hypothesis was accepted. This positive impact indicates that of the uses SIN will increase the achievement of accountability of KPP Pratama.